Innovative Recreational Game Development: Sport Monopoly Game for Enhancing Physical-Fitness Learning in Elementary Students - Miftahul Jannah; Yoso Wiyarno; Suharti (Universitas Negeri Surabaya, 2026)
Background: This study developed and evaluated an innovative recreational sport-based board game, the Sport Monopoly Game Physical Fitness, as a learning medium to enhance Grade V elementary students’ engagement and understanding of physical-fitness material during Physical Education (PJOK) lessons.. Methods: research and development (R&D) design adapted from the Borg & Gall model included needs analysis, data collection, product design, expert validation, small-group trials, iterative revisions, large-group field testing, and dissemination. Participants were Grade V students (classes VA/VB) at SDN Balongsari I/500, Surabaya (small group n = 14; large group n = 60). Data were collected through observation, needs-analysis questionnaires, student-response questionnaires, and documentation. Descriptive statistics (means and feasibility percentages) were calculated using Microsoft Excel, and qualitative comments were summarized. . Results: Small-group testing produced a total score of 893, a mean of 4.30 (“good”), and 86.9% feasibility. Large-group testing produced a total score of 1,595, a mean of 4.55 (“good”), and 91.15% feasibility. Prior expert validations showed feasibility values of 82.7% (material expert) and 83.6% (media expert). Conclusions: The Sport Monopoly Game Physical Fitness as an innovative recreational game, along with its guidebook, is feasible and suitable as supplementary media for Grade V PJOK physical-fitness lessons, and can enhance students’ enthusiasm for recreational sport-based learning and physical activity.